Rethinking adoptionism: an argument for dismantling a dubious category - Coogan, J (Cambridge University Press, 2023)
This article argues that adoptionism is an anachronistic category when used to describe texts from the first three Christian centuries, a mirage created by later theological controversies about the relationship between the Father and the Son. I survey the evidence for second- and third-century figures and texts generally identified ‘adoptionist’ in order to show that these figures do not advocate a shared christological stance. Instead, we find a variety of distinct postures that disagree with both each other and with common scholarly definitions of adoptionism. Although metaphors of adoption were theologically productive in early Christianity, to identify early Christian figures, texts and movements as adoptionist implies a theological unity that does not exist. The category itself is a problem. Not only are historical adoptionists absent, but early Christian metaphors of adoption and divine sonship functioned within diverse articulations of Jesus’ identity which do not map onto modern definitions.